Hubungan Perilaku Pemberantasan Sarang Nyamuk (PSN) 3M Plush Terhadap Kejadian Demam Berdarah Di Desa Tanjung Morawa A: Studi Cross-Sectional - Nanda, Meutia; Prisca, Della; Pratiwi, Sonya Tri; Annisyah, Wahyu; Salsabillah, Naila; Gunadi, Rizky (Yayasan Jompa Research and Development, 2025)
Dengue Hemorrhagic Fever (DHF) is one of the endemic diseases that continues to be a health problem in Indonesia, including in Tanjung Morawa A Village, Deli Serdang Regency. This study aims to analyze the relationship between community behavior in the Mosquito Nest Eradication (PSN) program and the incidence of DHF. The research method used was quantitative with a cross-sectional design, involving 97 respondents selected through stratified random sampling techniques. Data were collected through questionnaires and analyzed using the Chi-Square test. The results showed a significant relationship between the behavior of covering water reservoirs (p = 0.036), not hanging clothes (p = 0.002), the use of mosquito repellent (p = 0.037), and the installation of wire netting (p = 0.001) with the incidence of DHF. Meanwhile, other behaviors, such as draining the bathtub (0,500), using mosquito nets (0,173), and giving abate powder (0,694), did not show a significant relationship. These findings emphasize the importance of the active role of the community in implementing the 3M Plus PSN to reduce the incidence of DHF effectively.).